Evaluación del clima organizacional y su incidencia en el desempeño y desarrollo del talento humano por competencias en la empresa comercial zona franka S.A.” del cantón Santo Domingo de los Colorados, provincia de los Tsáchilas, año 2014 - Carrillo Sailema, Holger Franklin (2015)
The present research is the evaluation of organizational climate and it’s Effect on the Performance and Human Resource Development Competence it contributes to the continuous improvement plans Franka Trade Zone Company S.A. Located in the canton Santo Domingo de los Colorados, Tsáchilas Province. The general objective was wont, Evaluation Organizational Climate and its Impact on Performance and Human Resource Development Competency in Business Enterprise Zone Franka SA, in this way the work environment and work-organizational climate of the company diagnosis applying climate assessment indicators and job performance, in order to design a comprehensive system of emotional competencies and Talent Management competency. To determine the results we used the following methods: inductive deductive, analytic Synthetic as reflected in surveys applied to 65% of staff surveyed do not maintain a good working environment, so that the design a comprehensive system of emotional competencies talent management and improve the skills competency and job performance so that the working environment human Resource pleasant to improve the organizational climate. Motivated staffs in a pleasant work environment are the fundamental pillars on which successful organizations support their achievements, and to achieve this Comprehensive System of Emotional Skills and Talent Management is developed to maintain, amend or change attitudes and behaviors people within the organizations, addressed to the optimization of resources.